1996
DOI: 10.1007/bf02339007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of smectite composition on the catalysis of peptide bond formation

Abstract: Clay-catalyzed glycine and diglycine oligomerizations were performed as drying/wetting cycles at 80 degrees C. Two trioctahedral smectites (hectorite and saponite), three pure montmorillonites, a ferruginous smectite, an Fe(II)-rich smectite, and three smectites containing goethite admixture were used as catalysts. Highest peptide bond formation was found with trioctahedral smectites. About 7% of glycine was converted to diglycine and diketopiperazine on hectorite after 7 days. In the case of dioctahedral smec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 38 publications
3
34
0
Order By: Relevance
“…These results not only show the absolute need for the presence of Cu-II cations (as opposed to natural Na + ) for the polymerization to occur, but also show that ''clumping'' of glycine monomer into units large enough for SFM imaging does not occur during these cycling experiments (it may be that any clumps are washed away during the rehydration portions of the cycling experiments). This result, as well as other studies on the dependence of peptide yield on gallery cation species (Bujdàk and Rode 1996;Lahav et al 1978;Ripshon et al 1982), points to the definite role played by the gallery metal cations in the observed polymerization reactions.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…These results not only show the absolute need for the presence of Cu-II cations (as opposed to natural Na + ) for the polymerization to occur, but also show that ''clumping'' of glycine monomer into units large enough for SFM imaging does not occur during these cycling experiments (it may be that any clumps are washed away during the rehydration portions of the cycling experiments). This result, as well as other studies on the dependence of peptide yield on gallery cation species (Bujdàk and Rode 1996;Lahav et al 1978;Ripshon et al 1982), points to the definite role played by the gallery metal cations in the observed polymerization reactions.…”
Section: Resultssupporting
confidence: 56%
“…These layered silicates possess high surface areas, contain exchangeable metal cations, and readily adsorb and intercalate organic molecules. Of particular interest in the formation of peptides are experiments in which the prebiotic conditions of alternate heating and wetting cycles are simulated (Bujdàk and Rode 1996;Lahav et al 1978;Lawless and Levi 1979). In these studies, organic oligomers of up to 6 units have been extracted from the bulk clays and identified using techniques such as HPLC, gas chromatography, and mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%
“…In the heterogeneous phase (amino acids/clay), and using successive drying/wetting cycles, the reaction can occur at lower temperatures (about 100°C) (Chang et al 1978;Lawless and Levi 1979;White and Erickson 1981). Under optimal cation exchange conditions, glycine is essentially transformed into diketopyperazine and diglycine, in an overall yield not exceeding a few percent over a week (Bujdak and Rode 1996). These reactions have been extrapolated mainly in the glycine case and, to some extent, with alanine.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that the presence of clay mineral is necessary for the prebiotic reactions to proceed, and that the exchanged copper cations play an essential role in the peptide formation. Other studies on the dependence of peptide yield on gallery cation species (Bujdàk and Rode 1996, Lahav et al 1978, Ripshon et al 1982) also point to the definite role played by the gallery metal cations in the observed polymerization reactions.…”
Section: Resultsmentioning
confidence: 93%